BEYOND THE HORIZON: RECENT ADVANCES IN HOT MELT EXTRUSION TECHNIQUES AND TECHNOLOGIES - ABDO MOHSEN, MAGED MOHAMMED; PATIL, AMIT B.; ALKANAD, MAGED; PATIL, DARSHAN (International Journal of Applied Pharmaceutics, 2024)
This review article aims to explore the dynamic landscape of Hot Melt Extrusion (HME) technology, focusing on the spectrum of materials and machinery shaping innovation in the field. Polyethylene Oxide (PEO), Polyvinylpyrrolidones (PVP), Polypropylene (PP), Polyvinyl Acetate (PVA), and Polycaprolactone (PCL) play pivotal roles in HME and contribute to advancements in pharmaceutical manufacturing. This review sheds light on their unique contributions to HME tapestry. This review meticulously explored the machinery that orchestrates HME, including single- and double-screw extruders, as well as Extrusion Spheronization (ES). The search criteria were based on a comprehensive analysis of previous studies since the discovery of the HME, including new patented discoveries. We utilized various scholarly resources such as Google Scholar, Google Books, PubMed, Elsevier, Nature, Springer, ScienceDirect, and other indexed search engines. Case studies highlighted the real-world impact of HME in Continuous Manufacturing (CM) scenarios, emphasizing its importance in pharmaceutical production. The review also discusses the specifics of extrusion and co-extrusion, explaining how compound droplets are formed and collected, which is very important for making capsules-extrusion has emerged as a protagonist in the pharmaceutical industry, with 3D printing driving innovation beyond conventional boundaries. The amalgamation of HME and 3D printing offers new possibilities for drug delivery. This review sheds light on the diverse polymers involved in hot melt and emphasizes their importance in pharmaceutical manufacturing. This study provides valuable insights into the applications, methodologies, and future advancements of HME.